Wide-beam forming using binary phase coding - Woodman Pollitt, Ronald Francisco (2000)
In imaging work, it is desirable to have the transmitting beam width matched to the receiving one. One possibility to do this at Jicamarca, when single receiving modules are employed, is using one antenna module as the transmitting array (the whole Jicamarca array consists of 8 by 8 modules). However, with this solution one cannot transmit the high peak power available at Jicamarca (～2 MW). A second solution, where high transmission power is possible, consist on transmitting with ali the antenna modules, but using 4 different sets ofbinary cedes (0 or 180 phase delays), i.e., a two-dimensional complementary phase code. After the decoding process, the information obtained is equivalent to what one would obtain if the high power were transmitted on a single antenna module. The wide beam information is synthesized by adding the second-order statistics obtained with each set of codes. We have tested this idea at Jicamarca to get three-dimensional images of the tropopause and lower stratosphere. For transmission we have used four sets of codes, where each code consists of 4 by 4 elements.